2020
DOI: 10.1148/radiol.2020192534
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Nodal Evaluation in Breast Cancer: State of the Art

Abstract: Axillary lymph node (LN) metastasis is the most important predictor of overall recurrence and survival in patients with breast cancer, and accurate assessment of axillary LN involvement is an essential component in staging breast cancer. Axillary management in patients with breast cancer has become much less invasive and individualized with the introduction of sentinel LN biopsy (SLNB). Emerging evidence indicates that axillary LN dissection may be avoided in selected patients with node-positive as well as nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
162
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(167 citation statements)
references
References 120 publications
3
162
0
2
Order By: Relevance
“…Chang et al (3) suggested that axillary imaging warrants consideration of at least axillary level I or II to examine lymphadenopathy. A degraded muscular status may be indicative of a shorter time of progression (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chang et al (3) suggested that axillary imaging warrants consideration of at least axillary level I or II to examine lymphadenopathy. A degraded muscular status may be indicative of a shorter time of progression (34).…”
Section: Discussionmentioning
confidence: 99%
“…Because of its rapid progression and insidious symptoms in the early stage of biological invasion, breast cancer should be closely monitored with current advanced technology (2). The outcome of axillary lymph node dissection (ALND) plays an important role in the formulation and implementation of breast cancer regimens, including postoperative radiotherapy and chemotherapy (3). It is traditionally used for patients with metastatic sentinel lymph node (SLN) during surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Axillary US is the primary method for evaluation of axillary nodes, especially in the evaluation of early ALN metastasis. Breast MRI can better demonstrate lymph node metastasis on higher stations (19). However, the use of axillary US in evaluating ALN has been limited by its moderate accuracy and considerable discrepancy among the studies.…”
Section: Discussionmentioning
confidence: 99%
“…The predominant lymphatic drainage pathway drains from the breast toward the axilla (1). However, nodal metastases outside the axilla may be present in up to 56% of breast cancer patients (2). The sites of extra-axillary nodes include the internal mammary lymph nodes, the infraclavicular region, the supraclavicular fossa, the interpectoral (Rotter's) space, and the breast itself.…”
Section: Introductionmentioning
confidence: 99%